Hunger strikes and carceral resistance: embodied struggle, discourse, and the political meaning-making of hunger - Clark-Hargreaves, Becca, author; Sbicca, Joshua, advisor; Opsal, Tara, committee member; Cox-York, Kimberly, committee member (Colorado State University. Libraries, 2019)
Since 2014, there have been a series of hunger strikes at the Northwest Detention Center in Tacoma, WA. Hunger strikes have been utilized globally and throughout history, and, among other tactics, have been one of the primary tactics utilized by prisoners to protest their conditions and make broader political demands. In this study, I analyze the specific discursive repertoires created and deployed my media, detention officials, detainees, and one community activist organization surrounding the NWDC hunger strikes, in order to discover how hunger strikes operate as a mode of symbolic contestation. By delineating the specific frames constructed and deployed by each group, I construct an analysis of the dynamic and relational processes of discursive resistance and the ways that dominant and subaltern actors structure and contest the symbolic field surrounding immigration, detention, and carcerality. Overall, I find that detained hunger strikers and members of one grassroots solidarity organization draw upon a few primary discursive repertoires, including legalistic and rights-based discourses, and a discourse of family to contest hegemonic narratives of the hunger strikes. Finally, I draw upon the notion of differential consciousness to argue that subaltern actors engage in impure tactics of discursive resistance, deploying hegemonic languages only to subvert them, and in this way, challenging dominant narratives and the symbolic power of the state.
Keywords: hunger strikes; prison; detention centers; social movements; immigration